ANALISIS KADAR SERAT PADA BAKSO BEKATUL DENGAN METODE GRAVIMETRI - Hardiyanti; Nisah, Khairun (AMINA, 2019)
The goal of this study is to determine the level of fibre contained in bakso made from rice shiftings. The analysis employed gravimetric method with fibretherm apparatus. Firstly, the sample was defatted through n-hexanic soxhletation. After that,the gravimetric treatment was carried out in the apparatus to obtain the weight of the fibre. The data were then converted to percentage value. This step resulted the content of the fibre as following as 0.41; 0.23; 0.34; and 0.36% repectively for four samples. It shows that the level of those are below the standard of SNI 01-4439-1998.